1996
DOI: 10.3109/09540269609037823
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviour in childbearing women

Abstract: The first postnatal year is a period when the rate of psychiatric disorder is high, and a correspondingly high rate of suicide might be expected. Age-adjusted mortality ratios for suicide by women in the first postnatal year were therefore calculated from population data for England and Wales for a twelve-year period. The overall mortality ratio was found to be 17-that is, the actual total was one sixth of that expected. The low rate was not found after stillbirth which was associated with a rate of suicide si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
3
24
0
2
Order By: Relevance
“…The study found no significant gender difference in childlessness in elderly suicide victims which may imply that the protective effect of having children appears to diminish in old age. The lack of evidence for the protective effect of child bearing for elderly women in terms of suicide risk (Appleby, 1996;Catalan, 2000;Quin, 2000) is not surprising and could be explained by loss of maternal role due to children growing up and moving away from home. Of those not known to service, nearly half of men and women did not have GP contact in the 3 months prior to committing suicide.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…The study found no significant gender difference in childlessness in elderly suicide victims which may imply that the protective effect of having children appears to diminish in old age. The lack of evidence for the protective effect of child bearing for elderly women in terms of suicide risk (Appleby, 1996;Catalan, 2000;Quin, 2000) is not surprising and could be explained by loss of maternal role due to children growing up and moving away from home. Of those not known to service, nearly half of men and women did not have GP contact in the 3 months prior to committing suicide.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Factors associated with nonmedical death include intimate partner violence (IPV), which is reported to occur in 17%–27% of Australian pregnancies [12, 13], and perinatal anxiety and depression, with one in eight Australian women reporting depressive symptoms in the year following birth, and rates of diagnosed postnatal depression (PND) are reported to be 10% of Australian postnatal women [14]. Other contributing factors include mental health disorders and substance abuse [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Obsessive Ruminationen, das Kind verletzen zu können oder zu müssen, infantizide Vorstellungen, sind bei einigen Frauen aufzudecken, wenngleich das tatsächliche Risiko eines Infantizids als wohl sehr niedrig einzustufen, dann oft im Kontext einer erweiterten Suizidalität zu begreifen ist [15][16][17]. Das Suizidrisiko ist hoch, in einem Vergleich mit einer Kontrollgruppe von psychotischen Frauen in Nicht-Indexepisoden aber nicht signifikant erhöht [18]. Es muss insgesamt aber beachtet werden, dass das Suizidrisiko für Frauen mit postpartalen Psychosen im 1. postnatalen Jahr um das ca.…”
Section: Klinische Phänomenologie Der Postpartalen Psychosenunclassified